Kidney clamp, perfuse, re‐implant: a useful technique for graft salvage after vascular complications during kidney transplantation. (9th March 2015) - Mekeel, Kristin L.; Halldorson, Jeffery B.; Berumen, Jennifer A.; Hemming, Alan W.
Abstract Although intra‐operative vascular complications during renal transplantation are rare, injuries associated with prolonged ischemia may lead to graft threatening early and late complications. This series describes a novel technique for intra‐operative repair of vascular complications in five patients over a three‐yr period. The method consists of rapid graft nephrectomy and re‐preservation of the graft with cold University of Wisconsin solution, which allows for controlled/precise back table repair of the vascular injury without incurring prolonged warm ischemia time. In three cases, the donor renal vein (2) and donor renal artery (1) were damaged and required back table reconstruction. In two cases, the recipient iliac artery needed reconstruction. Three of the five cases used deceased donor iliac vessels from another donor for reconstruction. Two patients required postoperative dialysis for delayed graft function for three to nine d (average six d) and two patients had slow graft function. All grafts were functioning at 17 months (mean) after transplant, with a median serum of 1.61 mg/dL (0.74–3.69). This series demonstrates the effectiveness of kidney clamp, perfuse, resuscitate as an effective intra‐operative technique to salvage grafts after vascular injury. Although the grafts may suffer from delayed or slow graft function, excellent long‐term function is attainable.